Translation and psychometric evaluation of the Chinese version of the Digital Competence Questionnaire for clinical nurses - Zhengang Wei; Hongli Liu; Jicheng Zhang; Yan Chen; Lixia Chang; Huiyu Cheng; Xue Bai; Xiaohua Wang; Su Li (Digital Health)
Background Adequate digital competence is crucial for clinical nurses to effectively adapt to the evolving digital technologies in their practice. Currently, there is a lack of a brief assessment tool in China that comprehensively measures the digital competence of nurses in clinical practice across the dimensions of knowledge, skills, and attitudes. Therefore, this study aims to translate the Digital Competence Questionnaire (DCQ) into Chinese and evaluate its psychometric properties. Methods Following Brislin's translation model, the DCQ was translated and back-translated, and cultural adaptation and revisions of the Chinese version were conducted through expert consultations and a pilot survey. A cross-sectional study was carried out from July to October 2024 to conduct a methodological investigation on the translation and validation of the DCQ. Results The Chinese version of the DCQ includes two dimensions—attitude and knowledge & skills—with a total of 12 items. The overall Cronbach's α value for the questionnaire is 0.970, while Cronbach's α for the individual dimensions ranges from 0.921 to 0.945. The split-half reliability of the entire scale is 0.912, and the test–retest reliability is 0.846. Confirmatory factor analysis supported the hypothesized first-order two-factor model, with all fit indices demonstrating satisfactory values and remaining within acceptable levels. Conclusion The Chinese version of the DCQ has been successfully introduced in China, demonstrating strong psychometric properties. It can be used in healthcare settings as a tool to assess the digital competence of nurses, providing a basis for developing subsequent digital technology training programs and targeted interventions.